Catalytic dehydrogenative decarboxyolefination of carboxylic acids. Issue 12 (December 2018) - Sun, Xiang; Chen, Junting; Ritter, Tobias
Abstract Alkenes are among the most versatile building blocks and are widely used for the production of polymers, detergents and synthetic lubricants. Currently, alkenes are sourced from petroleum feedstocks such as naphtha. In light of the necessity to invent sustainable production methods, multiple approaches to making alkenes from abundant fatty acids have been evaluated. However, all attempts so far have required at least one stoichiometric additive, which is an obstruction for applications at larger scales. Here, we report an approach to making olefins from carboxylic acids, in which every additional reaction constituent can be used as a catalyst. We show how abundant fatty acids can be converted to alpha-olefins, and expand the method to include structurally complex carboxylic acids, giving access to synthetically versatile intermediates. Our approach is enabled by the cooperative interplay between a cobalt catalyst, which functions as a proton reduction catalyst, and a photoredox catalyst, which mediates oxidative decarboxylation; coupling both processes enables catalytic conversion of carboxylic acids to olefins. A direct conversion of carboxylic acids to alpha-olefins without the need for a stoichiometric additive has now been reported. The transformation is enabled by a dual cobalt/iridium proton-reduction–photoredox catalyst system, and can proceed on abundant fatty acids as well as on complex carboxylic acids.